2004
DOI: 10.1071/ea03115
|View full text |Cite
|
Sign up to set email alerts
|

Grain grower perceptions and use of integrated weed management

Abstract: Greater adoption of integrated weed management, to reduce herbicide reliance, is an objective of many research and extension programmes. In Australian grain-growing regions, integrated weed management is particularly important for the management of herbicide resistance in weeds. In this study, survey data from personal interviews with 132 Western Australian grain growers are used to characterise the use and perceptions of integrated weed management practices. The main objective was to identify opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…It should be recognised that only a minority of no-tillage adopters use no-tillage across their whole cropping program, with cultivation still used to some extent by most growers. Results by Llewellyn et al (2004) suggest cultivation is often used with the intention of achieving some weed control. However, in regions where the proportion of growers adopting no-tillage is increasing, the use of cultivation for weed control will be in decline.…”
Section: Discussionmentioning
confidence: 99%
“…It should be recognised that only a minority of no-tillage adopters use no-tillage across their whole cropping program, with cultivation still used to some extent by most growers. Results by Llewellyn et al (2004) suggest cultivation is often used with the intention of achieving some weed control. However, in regions where the proportion of growers adopting no-tillage is increasing, the use of cultivation for weed control will be in decline.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that even farmers who have not experienced herbicide resistance on their farm hitherto show pro‐active behaviour in terms of their resistance management. This is in contrast to the general assumption that farmers tend to avoid the adoption of management strategies until the first resistant weeds are recognized on their farm . The percent of farmers using each of the ten resistance management strategies is presented in Table .…”
Section: Resultsmentioning
confidence: 97%
“…This is in contrast to the general assumption that farmers tend to avoid the adoption of management strategies until the first resistant weeds are recognized on their farm. 13,14 The percent of farmers using each of the ten resistance management strategies is presented in Table 5. The three most commonly adopted strategies were rotation of MoA over the crop rotation (89%), rotation of cereals and dicotyledonous crops (76%) and rotation of MoA within the crop (64%).…”
Section: Cluster Analysis Of Resistance Management Strategiesmentioning
confidence: 99%
“…Surveys have been conducted to assess grower perceptions about the issues and implications of herbicide resistance, weeds, tillage, and integrated approaches for weed management Llewellyn et al 2002Llewellyn et al , 2004. For example, a robust survey conducted in six states in the USA reported that growers in the Midwest are more likely to adopt crop rotation to address weed management problems than growers in the Southeast ).…”
Section: Implications and Grower Perceptionsmentioning
confidence: 99%
“…Surveys reported that in the Australian grain-growing regions, growers had awareness of HR weeds and ascribed a high economic cost to herbicide resistance (Llewellyn et al 2002). Growers in Australia were adopting IWM and perceived that these tactics had economic value (Llewellyn et al 2004). However, practices that included alternative herbicides were perceived to have the highest economic return on investment and growers felt that a stock of new herbicides would be developed in the short term to better manage the building HR weed populations (Llewellyn et al 2002(Llewellyn et al , 2004.…”
Section: Implications and Grower Perceptionsmentioning
confidence: 99%